2021
DOI: 10.1002/jcla.23883
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of the ratio of the product of neutrophils and hemoglobin to lymphocytes in non‐muscular invasive bladder cancer patients with postoperative recurrence

Abstract: Purpose The purpose of this study was to explore the predictive value of the ratio of the product of neutrophils and hemoglobin to lymphocytes (NHL) in patients with non‐muscular invasive bladder cancer (NMIBC). Materials and Methods We retrospectively collected clinical and pathological data of patients with NMIBC who underwent transurethral resection of bladder tumor (TURBT) at our hospital between 2013 and 2018. The ratio of neutrophils to lymphocytes (NLR), the Systemic Immune Inflammation Index (SII), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Full texts of 17 studies were then reviewed, with 7 studies excluded. Finally, 10 studies that comprised 7,087 patients were included in this meta-analysis ( 9 13 , 16 20 ). All the included studies have been published within the last 3 years (2019–2021); five studies focused on NMIBC ( 11 , 16 , 17 , 19 , 20 ) and the other five studies on MIBC ( 9 , 10 , 12 , 13 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Full texts of 17 studies were then reviewed, with 7 studies excluded. Finally, 10 studies that comprised 7,087 patients were included in this meta-analysis ( 9 13 , 16 20 ). All the included studies have been published within the last 3 years (2019–2021); five studies focused on NMIBC ( 11 , 16 , 17 , 19 , 20 ) and the other five studies on MIBC ( 9 , 10 , 12 , 13 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 10 studies that comprised 7,087 patients were included in this meta-analysis ( 9 13 , 16 20 ). All the included studies have been published within the last 3 years (2019–2021); five studies focused on NMIBC ( 11 , 16 , 17 , 19 , 20 ) and the other five studies on MIBC ( 9 , 10 , 12 , 13 , 18 ). Notably, all of the 10 studies were retrospective, and six of them had been conducted in China ( 9 , 11 , 12 , 16 , 19 , 20 ), two in Europe and United States ( 10 , 17 ), one in Turkey ( 13 ), and one in Japan ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was reported that a higher NLR was associated with an increased risk of disease recurrence and progression in patients with bladder cancer (21,22). Zhao et al indicated that tumor tissue stimulated the production of neutrophils, which could promote tumor cell proliferation and angiogenesis by releasing cytokines and effector molecules, especially interleukins and the pro-angiogenic vascular endothelial growth factor (23). Meanwhile, a decreased lymphocyte level could weaken adaptive immune responses towards the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a decreased lymphocyte level could weaken adaptive immune responses towards the tumor. The combined effects of these two cellular mechanisms indicated that the NLR reflected the results of antagonism between inflammatory responses and antitumor effects and therefore had a certain prognostic value for tumors (23). Blood cell count is routinely tested for hospitalized patients, so it required no additional cost or patient inconvenience (22).…”
Section: Discussionmentioning
confidence: 99%